Prevalence and correlates of diabetes distress, perceived stress and depressive symptoms among adults with early‐onset Type 2 diabetes: cross‐sectional survey results from the Danish DD2 study. Issue 10 (16th August 2019) - Bo, A.; Pouwer, F.; Juul, L.; Nicolaisen, S. K.; Maindal, H. T.
Abstract: Aims: To establish the prevalence of diabetes distress, perceived stress and depressive symptoms among adults with early‐onset Type 2 diabetes, and to examine their association with socio‐demographic and clinical characteristics. Methods: A cross‐sectional survey was performed among individuals with Type 2 diabetes aged 20‐45 years who were included in the Danish nationwide Danish Center for Strategic Research in Type 2 Diabetes cohort between 2010 and 2016. The survey assessed diabetes distress (20‐item Problem Areas in Diabetes Scale), perceived stress (10‐item Perceived Stress Scale) and depressive symptoms (10‐item short form of the Center for Epidemiological Studies Depression Scale Revised), as well as socio‐demographic characteristics. Clinical data were collected from national health registers. Results: In total, 216/460 (47%) individuals (48% women) with Type 2 diabetes completed the survey. The median (IQR) age was 42 (38–44) years and the diabetes duration was 5 (3–7) years. In total, 24% of respondents reported high diabetes distress (Problem Areas in Diabetes Scale ≥ 40), 46% reported high perceived stress (Perceived Stress Scale ≥ 18) and 41% reported elevated symptoms of depression (Center for Epidemiological Studies Depression Scale Revised ≥ 10). The prevalence of emotional problems was higher among women than men. Diabetes distress was higher among those prescribed non‐insulin glucose‐lowering drugs (vs. no glucose‐lowering drugs), but was not associated with other clinical or socio‐demographic characteristics. High perceived stress was associated with being unemployed and using antidepressant medication, and elevated depressive symptoms were associated with low education level, unemployment, living alone, having a psychiatric disorder and using antidepressant medication. Conclusion: We found a high prevalence of emotional problems among adults with early‐onset Type 2 diabetes in Denmark. Health care for this group should focus on both physical health and psychosocial circumstances and should also address general as well as diabetes‐specific emotional problems. What's new?: Adults with early‐onset Type 2 diabetes have an adverse risk factor profile. In Denmark, data on their psychosocial profile are needed to develop adequate health services. Almost half of 216 adults aged 20–45 years with Type 2 diabetes reported high levels of perceived stress and depressive symptoms, while a quarter reported high diabetes distress. The prevalence of emotional problems was higher among women and among some groups of lower socio‐economic status. Health services should be adapted to meet life‐stage specific needs in this group and to integrate psychosocial aspects into diabetes care. Gender‐specific interventions may be needed.